Analisis Preferensi Konsumen Terhadap Produk Bath Bomb Salt Lemongrass di Kabupaten Bangkalan, Madura - Maflahah, Iffan; Hidayati, Meilina; Fakhry, Muhammad; Asfan, Dian Farida (JURNAL AGROTEKNOLOGI, 2023)
Bath bomb salt is a processed salt product and is a new product. New products need to test consumer preferences so that the product circulated follows the wishes of consumers. Consumer preferences are used to increase the effectiveness of marketing products or services. This study aims to determine consumer preferences for bath bomb salt lemongrass products and analyze consumer preferences using the conjoint analysis method on bath bomb salt products. The research method used is the conjoint method. The research was conducted in Bangkalan Regency and used 100 respondents. Based on the results of the research, it can be found that consumer preference attributes include color (varies), usage effect (safe for skin), benefits (removes dirt on the skin), and main ingredients (Epsom salt, sodium bicarbonate and citric acid). The order of consumer preferences for bath bomb salt lemongrass products is color with a weight value of 34.875%, benefits with a weight value of 22.733%, main ingredients with a weight value of 22.158%, and usage effects with a weight value of 20.234%. Keywords: bath bomb salt, conjoint analysis, consumer preferences